(untitled) (The Agriculturists, 2019)
An experiment was conducted at the farmer’s field in Shibalaya upazilla of Manikganj district during rabi season of 2017to study the effectiveness of biochar on soil fertility and yields of brinjal and cauliflower. There were five treatments viz. control, recommended inorganic fertilizer (RF), biochar 1 t/ha + RF, biochar 3 t/ha + RF and biochar 5 t/ha + RF laid out in a randomized complete block design with four replications. Data revealed that biochar at the rate of 5 t/ha along with RF provided maximum yields of brinjal (67 t/ha) and cauliflower (42 t/ha). The pH, nutrients and moisture contents of the study soils increased and bulk density decreased with the higher rates of biochar application. Significant changes were observed in the total organic carbon in soils which increased by 25 to 41% from the initial levels. Recovery, agronomic and physiological efficiencies of N, P, K and S were found the highest with the application of biochar 5 t/ha. In terms of soil fertility and crop productivity application of biochar was found promising and can be recommended as an effective soil management practice. The Agriculturists 2019; 17(1-2) 76-88